How work efficiency changes during a summer season with roller skiing training and its influence on performace - Jensen, K.; Höök, M.; Wedholm, L.; Björklund, G.; Holmberg, H. C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Test procedures involving submaximal and maximal treadmill rotier skiing as an exercise model for estimating a physiological profile are valuable tools in evaluating training adaptations in skiers during different parts of the season (Holmberg, 2005). The standardization of equipment, especially by using the same rollerskis that have been controlled for friction coefficient (Ainegren, 2008) has to be taken into consideration. However, when going from snow to "dry" land training, changes in work efficiency for individual skiers could influence the outcome. The purpose of the study was to evaluate performance changes over the summer season by including work efficiency measurements.